STEM-Based Guided Inquiry in Colloid Practicums and Its Influence on Students' Concept Mastery - Sulastri, Sulastri; Mohamad Sattar Rasul; Juliana; Syahrial; Ismi Zatya (Jurnal Pendidikan IPA Indonesia, 2025)
The rapid development of science and technology in the 21st century necessitates an educational approach that fosters students' critical thinking, problem-solving, and conceptual mastery skills, particularly in complex topics such as colloids. This study aims to examine the effectiveness of applying a STEM-based guided inquiry approach in colloid practicums on improving students' conceptual mastery. The research design used was a quasi-experimental pretest-posttest control group study involving 34 second-semester students in the Chemistry Education Program at UIN Ar-Raniry. The research instruments consisted of a two-level multiple-choice concept mastery test and a STEM learning effectiveness questionnaire. The study was conducted over six weeks through several colloid laboratory sessions. Statistical analysis using ANCOVA (p < 0.005) showed a significant difference in posttest scores between the experimental and control groups. The high effect size (Cohen's d = 0.8) indicates that this approach has a significant impact on student learning outcomes, particularly in developing higher-order thinking skills at levels C4 to C6. This study indicates that integrating a contextual, student-centered STEM-based learning model into chemistry laboratory sessions can enhance conceptual understanding and 21st-century skills. However, limitations such as a small sample size, research location restricted to a single institution, and relatively short treatment duration should be considered when generalizing the study's findings. Further research with a longitudinal design and a broader sample scope is highly recommended.